Publishing the cult of St Frideswide in eleventh- and twelfth-century Oxford - Dunning, A (Brepols, 2024)
The canons of St Frideswide’s Priory in Oxford relaunched a pilgrimage cult centred on their patron through a series of publications whose manuscript evidence only hints at a broader publishing programme. A Life of St Frideswide (BHL 3164) added to the Worcester Legendary is proposed as an eleventh-century work by an outsider, possibly from the period in which Abingdon Abbey controlled the community. This was the main source available for Frideswide in the middle of the twelfth century, when Robert of Cricklade wrote a more sophisticated and ambitious life based on this text (BHL 3162), one of several works that used publishing networks to manoeuvre through the administrative challenges of a new religious foundation, competition with Osney Abbey, the Anarchy, and the Becket controversy. The creation of a pilgrimage cult in Canterbury from 1170 was deeply influential on Oxford, as reflected in Prior Philip’s Miracles of St Frideswide (BHL 3169), which was written to demonstrate the success of the cult and its appeal to a wide range of devotees after the translation of Frideswide’s relics in 1180. While these had comparably limited circulation, material evidence demonstrates how these works supported broader textual communities to successfully promote a pilgrimage cult that aimed to compete with that of Thomas Becket.